Digital Image Correlation Compatible Mechanoluminescent Skin for Structural Health Monitoring (Adv. Sci. 11/2022). Issue 11 (14th April 2022) - Shin, Ho Geun; Timilsina, Suman; Sohn, Kee‐Sun; Kim, Ji Sik
Abstract : Structural Health Monitoring The compatibility of mechanoluminescent (ML) skin with the digital image correlation (DIC) algorithm under UV exposure is leveraged to quantify the ML effects in terms of effective strain. The calibration can be executed using the same photographic image. Interestingly, a linear correlation exists despite the plastic flow in ML skin. The quantification extends the ML application from visualizing strain concentration zones to quantitative measurement. More details can be found in article number 2105889 by Suman Timilsina, Ji Sik Kim, and co‐workers.